Keefektifan Dosis Kaporit [Ca(OCL)2] Dalam Menurunkan Kadar Amoniak (NH3) Pada Limbah Cair Rumah Sakit PKU Muhammadiyah Surakarta - Aminullah, Muhammad; , Heru Subaris K, SKM., M.Kes; , Dwi Astuti, SKM., M.Kes (2015)
Levels of ammonia (NH3) waste water PKU Muhammadiyah Surakarta Hospital has more than raw quality that has been set. After the test was obtained the results of the measurement of levels of ammonia in the PKU Muhammadiyah Surakarta Hospital got the results of 1,775 mg/l. According to the Regional Central Java province number 5 2012 about water quality standard waste hospital in central Province determined. Value to the parameters of ammonia by 0.1 mg/l.The purpose of this research is to know effectiveness of a dose of chlorine in lowering levels of ammonia liquid waste hospital. A method of the research is true research experiment with pre - post test with control design. Processing using chlorine in with a dose of 5 gr/l, 10 gr/l, and 15 gr/l with a method of slow manual stirring 10 rpm 10 minutes. The number of samples being tested as many as 24 samples, technique with the taking of specified the size of the sample with the quota of sampling. Using test statistic of one-way anova obtained value p-value 0,000 < α = 0,01 showed no difference in the level of controls, and treatment ammoniac between groups before and after the liquid waste processing PKU Muhammadiyah Surakarta Hospital. From test results showing a dose of lsd effective to lower ammonia levels of 5 g/l. Keywords : ammonia, chlorine, the liquid waste hospital.